Financial Statement Fraud Detection: The Hexagon Fraud Model Approach - Yulianti, Yulianti; Sari, Ratna Novita; Santoso, Aprih; Ekdjaja, Margarita; Rorlen, Rorlen (Pusat Penerbitan dan Publikasi Ilmiah, FEB, Universitas Muslim Indonesia, 2024)
The purpose of this study is to examine the likelihood of financial statement fraud using the fraud hexagon model, including pressure (financial stability), opportunity (ineffective monitoring), rationalization (auditor change), capability (director change), arrogance (frequent CEO pictures), and conspiracy (connection with government projects) on financial statement fraud. The sample of this study is manufacturing companies listed on the Indonesian Stock Exchange from 2019 to 2021, with a total of 73 companies. The data was processed using SPSS 22 software. The results of this study indicate that financial stability has a positive effect on financial statement fraud. However, ineffective monitoring, change of auditor, change of directors, frequent number of CEO pictures, and connection with government projects do not affect financial statement fraud.